2016
DOI: 10.1097/mib.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function of Patients with Crohnʼs Disease is Associated with Intestinal Disease Activity

Abstract: Cognitive performance is related to CD activity and nutritional status. The results provide insight into potential influence of nutrition and inflammation on cognitive function. Further studies on cognitive function of patients with CD are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Thus, the MS cohort did appear to experience lower cognitive functioning compared to the other disease cohorts, though not necessarily at a level that met a formal threshold for impairment. Previous studies have also reported deficits in processing speed in IBD, 30 and deficits in verbal memory in IBD and RA, in keeping with our findings. 12,31 Working memory was the only cognitive domain examined in the current study in which elevated rates of impairment were not seen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the MS cohort did appear to experience lower cognitive functioning compared to the other disease cohorts, though not necessarily at a level that met a formal threshold for impairment. Previous studies have also reported deficits in processing speed in IBD, 30 and deficits in verbal memory in IBD and RA, in keeping with our findings. 12,31 Working memory was the only cognitive domain examined in the current study in which elevated rates of impairment were not seen.…”
Section: Discussionsupporting
confidence: 93%
“…29 The CVLT-II assesses the capacity to learn and remember verbal information, the LNS assesses working memory capacity, and the SDMT assesses processing speed. These measures were chosen to assess cognitive domains commonly reported as affected in those with MS, IBD, RA, 4,[30][31][32] and anxiety and depression disorders. 21 The Wechsler Test of Adult Reading (WTAR) 33 was included to estimate premorbid (i.e., relatively resistant to brain disease) cognitive functioning, based on single word reading.…”
Section: Methodsmentioning
confidence: 99%
“…The interconnectivity of the brain‐gut axis is further suggested as IBD symptoms correlate to stress, which in turn correlates to changes in the hypothalamic‐pituitary‐adrenal axis, prefrontal amygdaloid complex, and CRFergic system . Furthermore, significant associations between markers of CD progression, cognitive dysfunction, and stress levels have been described in patients with CD . One particular study, which compared asymptomatic IBD adolescent patients to their control counterparts, suggested that those with IBD tended to have lower grade point averages and more difficulty in some areas of school functioning compared to healthy youth .…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Furthermore, significant associations between markers of CD progression, cognitive dysfunction, and stress levels have been described in patients with CD. 8 One particular study, which compared asymptomatic IBD adolescent patients to their control counterparts, suggested that those with IBD tended to have lower grade point averages and more difficulty in some areas of school functioning compared to healthy youth. 9 Adult patients with IBD have also demonstrated lower verbal IQ scores compared to healthy controls (HCs), as well as controls with IBS, predicting that the disease process of IBD could be responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Golan et al . found declines in verbal function and data processing speed compared to the normative data of healthy subjects 16 . Langenberg et al .…”
Section: Discussionmentioning
confidence: 76%